Prognostic nomogram incorporating radiological features for predicting overall survival in patients with AIDS-related non-Hodgkin lymphoma. Issue 1 (5th January 2022) - Li, Xueqin; Pan, Ziang; Wang, Xing; Hu, Tianli; Ye, Wen; Jiang, Dongmei; Shen, Wen; Liu, Jinxin; Shi, Yuxin; Xia, Shuang; Li, Hongjun
Abstract : Supplemental Digital Content is available in the text Abstract: Background: Acquired immune deficiency syndrome (AIDS)-related non-Hodgkin lymphoma (AR-NHL) is a high-risk factor for morbidity and mortality in patients with AIDS. This study aimed to determine the prognostic factors associated with overall survival (OS) and to develop a prognostic nomogram incorporating computed tomography imaging features in patients with acquired immune deficiency syndrome-related non-Hodgkin lymphoma (AR-NHL). Methods: A total of 121 AR-NHL patients between July 2012 and November 2019 were retrospectively reviewed. Clinical and radiological independent predictors of OS were confirmed using multivariable Cox analysis. A prognostic nomogram was constructed based on the above clinical and radiological factors and then provided optimum accuracy in predicting OS. The predictive accuracy of the nomogram was determined by Harrell C-statistic. Kaplan–Meier survival analysis was used to determine median OS. The prognostic value of adjuvant therapy was evaluated in different subgroups. Results: In the multivariate Cox regression analysis, involvement of mediastinal or hilar lymph nodes, liver, necrosis in the lesions, the treatment with chemotherapy, and the CD4 ≤100 cells/μL were independent risk factors for poor OS (all P  < 0.050). The predictive nomogram based on Cox regression has good discrimination (Harrell C-index = 0.716) and good calibration (Hosmer–Lemeshow test, P  = 0.620) in high- and low-risk groups. Only patients in the high-risk group who received adjuvant chemotherapy had a significantly better survival outcome. Conclusion: A survival-predicting nomogram was developed in this study, which was effective in assessing the survival outcomes of patients with AR-NHL. Notably, decision-making of chemotherapy regimens and more frequent follow-up should be considered in the high-risk group determined by this model.